1995
DOI: 10.1001/jama.1995.03520380042033
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up Results of a Randomized Drug Abuse Prevention Trial in a White Middle-class Population

Abstract: Drug abuse prevention programs conducted during junior high school can produce meaningful and durable reductions in tobacco, alcohol, and marijuana use if they (1) teach a combination of social resistance skills and general life skills, (2) are properly implemented, and (3) include at least 2 years of booster sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
388
0
25

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 717 publications
(436 citation statements)
references
References 28 publications
15
388
0
25
Order By: Relevance
“…Reliability (K-R 20) for the SII at the follow-up assessment 5½ years past baseline was in the range expected for this type of index (0.58- . Prior studies have reported the use of similar substance use indices and their predictive validity (Spoth et al, 1999;Trudeau et al, 2003), consistent with the general literature on the validity of such self-report measures (e.g., Botvin et al, 1995;Elliott et al, 1983;Williams et al, 1995).…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…Reliability (K-R 20) for the SII at the follow-up assessment 5½ years past baseline was in the range expected for this type of index (0.58- . Prior studies have reported the use of similar substance use indices and their predictive validity (Spoth et al, 1999;Trudeau et al, 2003), consistent with the general literature on the validity of such self-report measures (e.g., Botvin et al, 1995;Elliott et al, 1983;Williams et al, 1995).…”
Section: Methodssupporting
confidence: 67%
“…This study incorporated a multicomponent intervention, addressing such factors in both socializing environments. The intervention consisted of two theory-based programs: the Strengthening Families Program: For Parents and Youth 10-14 (SFP 10-14; Molgaard et al, 2000); and Life Skills Training (LST; Botvin et al, 1995), a school-based universal intervention. Together they target a wide range of empirically-and theoretically-supported factors (e.g., family-, individual-, peer-, and school-related) associated with adolescent substance use.…”
Section: Introductionmentioning
confidence: 99%
“…Group-based interventions have been shown to have beneficial effects (Botvin, Baker, Botvin, & Diaz, 1995, for school-based interventions to prevent adolescent drug use; Kelly et al, 1997, for community-based interventions to prevent HIV; and Ialongo et al, 1999, for classroom-based interventions to prevent aggression and school achievement), including effects that can be obtained through``social norms marketing'' as described by Dr. Mann. However, group-based interventions can result occasionally in harmful effects (Dishion, McCord, & Poulin, 1999, for drug use).…”
Section: What Can Be Learned From Other Prevention Research Approachementioning
confidence: 99%
“…Prevention approaches designed to decrease the impact of social influences to use tobacco, alcohol, and illicit drugs by teaching resistance skills and antisubstance use norms either alone or in combination with teaching generic personal selfmanagement skills and social skills have been shown to significantly reduce the rate of adolescent substance use (Botvin & Griffin, 2003). In some instances, reductions in substance use have been observed for over five years (Botvin, Baker, Dusenbury, Botvin, & Diaz, 1995;Griffin, Botvin, & Nichols, 2006). Moreover, evidence from recent follow-up studies testing universal, school-based prevention approaches demonstrates the potential of these interventions for preventing multiple problem behaviors, including some not directly targeted.…”
mentioning
confidence: 99%